IMPLEMENTASI SISTEM SELEKSI CALON SISWA DENGAN ALGORITMA SIMPLE ADDITIVE WEIGHTING BERBASIS WEBSITE (STUDI KASUS: SMP BENTENG BETAWI) - Imam Fachrudin Quraisi; Dede Sahrul Bahri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
In the era of globalization driven by the rapid development of information technology, the adoption of technology in various sectors, including education, has become very urgent. Information technology not only supports the learning process but also optimizes administrative aspects, such as the selection of prospective new students. Manual selection is often slow, error-prone, and non-transparent. Therefore, implementing technology-based systems becomes relevant. Benteng Betawi Middle School is committed to implementing a modern, efficient and transparent selection system using the website-based Simple Additive Weighting (SAW) algorithm. The SAW algorithm, as a simple and effective multi-criteria decision making method, is expected to speed up data processing, increase the accuracy and transparency of selection, and identify the best prospective students. This research aims to design and implement a website-based student selection system using the SAW algorithm at Benteng Betawi Middle School. The steps taken include needs analysis, design, implementation and system evaluation. It is hoped that this system can increase the efficiency, transparency and objectivity of the selection process at Benteng Betawi Middle School and become a reference for other schools that wish to adopt similar technology.